Reliability of horizontal force-velocity-power profiling during short sprint-running accelerations using radar technology - Simperingham, K. D.; Cronin, J. B.; Pearson, S. N.; Ross, A. (Sports Biomechanics, 2019)
Radar technology can be used to perform horizontal force-velocity-power profiling during sprint-running. The aim of this study was to determine the reliability of radar-derived profiling results from short sprint accelerations. Twenty-seven participants completed three 30 m sprints (intra-day analysis), and nine participants completed the testing session on four separate days (inter-day analysis). The majority of radar-derived kinematic and kinetic descriptors of short sprint performance had acceptable intra-day and inter-day reliability [intraclass correlation coefficient (ICC) = 0.75 and coefficient of variation (CV) = 10%], but split times over the initial 10 m and some variables that include a horizontal force component had only moderate relative reliability (ICC = 0.49-0.74). Comparing the average of two sprint trials between days resulted in acceptable reliability for all variables except the relative slope of the force-velocity relationship (S Fvrel; ICC = 0.74). Practitioners should average sprint test results over at least two trials to reduce measurement variability, particularly for outcome variables with a horizontal force component and for sprint distances of less than 10 m from the start.